Optimal Timing of Perioperative Chemoprophylaxis in Patients With High Thromboembolic Risk Undergoing Major Abdominal Surgery: A Multicenter Cohort Study. Issue 1 (5th January 2023) - Liu, David S.; Stevens, Sean G.; Watson, David I.; Goh, Su Kah; Muralidharan, Vijayaragavan; Wong, Enoch; Fong, Jonathan; Wong, Darren J.; ,; ,
Abstract : Objective: To determine whether early (before skin closure) versus postoperative chemoprophylaxis affects the incidence of venous thromboembolism (VTE) and bleeding following major abdominal surgery, in a high thromboembolic risk population. Background: Major abdominal surgery incurs both VTE and bleeding risks. Patients with high preoperative VTE risk derive the most benefit from chemoprophylaxis, but carry an increased risk of bleeding. The optimal window for chemoprophylaxis in the perioperative period, whereby both VTE and bleeding risks are minimized, is unknown. Methods: Analysis of pooled data from 5 multicenter studies including only high thromboembolic risk (Caprini score >4) patients. Clinical VTE was defined as radiographically proven symptomatic disease <30 days postsurgery. Major bleeding was defined as the need for blood transfusion, reintervention, or >20 g/L fall in hemoglobin. Results: From 5501 cases, chemoprophylaxis was initiated early in 1752 (31.8%) patients and postoperatively in 3749 (68.2%) patients. Baseline characteristics were similar between study groups. The incidence of clinical VTE was not associated with chemoprophylaxis timing [early 0.7% vs. postop 0.7%, odds ratio (OR): 1.11, 95% confidence interval (CI): 0.60–2.15, P =0.730]. Contrastingly, compared with postoperative chemoprophylaxis, early usage increased the risk of all bleeding (5.1% vs. 2.6%, OR: 2.04, 95% CI: 1.52–2.73, P <0.001) major bleeding (3.6% vs. 1.8%, OR: 1.99, 95% CI: 1.40–2.81, P <0.001), and reintervention (2.0% vs. 1.0%, OR: 2.10, 95% CI: 1.32–3.35, P =0.003). Early chemoprophylaxis independently predicted postoperative bleeding (OR: 1.71, 95% CI: 1.25–2.34, P <0.001), but not VTE. Conclusions: In high VTE risk patients undergoing major abdominal surgery, chemoprophylaxis commenced postoperatively reduces bleeding risk without affecting clinical VTE risk.